Water Quality and Plankton Composition of Amblypharyngodon mola Monoculture Fish Pond in Bangladesh - Hoque, Md Mozzammel; Motin, Md Abdul; Majnoonnaher, Maya; Sarkar, Md Reaz Uddin; Islam, Md Rafiqul; Chowdhury, Muhammad Tanvir Hossain; Khan Chowdhury, Ahmed Jalal (IJETTCS, 2014)
A study was conducted to assess the water quality and plankton composition in Amblypharyngodon mola fish pond for a period of 4 months in Bangladesh. Nine earthen pond each with three treatments, viz. T1, T2 and T3 were stocked with A. mola at the density of 145,000; 73,000 and 36,500 individual ha-1, respectively. Water quality parameters such as water temperature, transparency, total alkalinity, pH, dissolved oxygen, Nitrate- nitrogen, ammonia-nitrogen, phosphate-phosphorus and chlorophyll-a of the ponds water were measured. Water quality parameters (except transparency and chlorophyll-a) did not show any significant differences (P> 0.05) among the treatments. The lowest PO4-P and chlorophyll-a concentration were observed in treatment T1 where 145,000 individual ha-1 of A. mola was cultured. Plankton samples were also collected and identified throughout the study period. A total of 38 genera of phytoplankton and 13 genera of zooplankton were identified of which Chlorophyceae (20 genera) in phytoplankton population and Crustacea (9 genera) in zooplankton population were dominant. The mean value of total plankton population (× 103 cells L-1) were 158.42 53.33, 191.17  62.24 and 240.17  93.37 in T1, T2 and T3 treatments, respectively and contributing to the fish production according to their availability and abundance within the treatment. The study reveals that the rural based farmers can develop an actual mechanism of plankton production in aquatic environment which could be essential necessary for the maintenance of water quality and sustainable development of small scale indigenous fish culture in Bangladesh and other developing countries.